BIMBINGAN TEKNIS PEMASANGAN PERANGKAT SPC CAMERA MODEL KST2 UNTUK KEAMANAN WARGA PERUMAHAN CITRA CANDI MENDUT MALANG - Indrawan Nugrahanto; Sungkono; Elka Faizal (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
At this time the demand for security cameras is increasing in line with the increasing number of criminal acts, this technology seems to be required to be installed in various public places and facilities that require more supervision in order to create security and safety. IP Camera (type KST2 SPC) is the latest solution in the field of security. This monitoring device has a monitor range that is not limited to the room, but the IP camera can also be accessed by a personal computer or laptop that is connected directly via LAN, Internet, or cellular network. IP Camera is a long-term solution that is very useful, very flexible, and can work for the next 10 years. IP Camera has other features such as camera selection and navigation features that affect video size and access speed. IP Camera is a CCTV (Closed Circuit Television) camera that uses Internet Protocol to transmit image data and control signals. Thus, IP cameras have several advantages over analog CCTV. In its use, this tool is also quite easy to integrate with various electronic-based early warning systems. Data from camera readings can be stored on a microSD which can store recording activity data for a full month.